dene ghagonete - Fabian, Roy; Gaudet, Sarah; Harley, Shirley; Horne, Irene; Horesay, Christine; McCauley, Vivian; Norwegian, Andy; Norwegian, Gladys; Tucho, Judy (Slavey writer's workshop, 1976)
https://www.sil.org/resources/archives/15913